Public relations in liquid modernity: How big data and automation cause moral blindness. (September 2019) - Bachmann, Philipp
Despite coming from a world-famous, widely published sociologist and ethicist, Zygmunt Bauman's thought has not significantly influenced scholarship on public relations. Although Bauman's works indeed challenge classical theories of public relations, they also offer concepts that can reshape current understandings of how organisations interact with publics. Referring to Bauman's social and ethical theory, in this article, I argue that amid the transition from solid to liquid modernity, the boundaries between public relations and other communications disciplines also become liquid and ultimately dissolve. As a consequence, experts from traditional disciplines within communications (e.g. public relations, marketing and corporate communications) increasingly compete with data engineers to influence publics, and in the process, their attempts at persuasive communication neglect moral considerations. In light of that dynamic, I contend that the recent data scandal involving Cambridge Analytica does not represent a false start but the dark future of digital communications management.